Perancangan Sistem Pengarsipan Dokumen Administrasi Perangkat Pembelajaran Guru Berbasis Web di SMK Citra Bangsa Bogor - Wahyuni Aprilia; Kussigit Santosa (CV. Multi Kreasi Media, 2022)
Every year the school will definitely have new documents, especially on teacher learning tools. The archiving process that occurs is still doing manual storage where documents in hard copy are collected at the Deputy Principal for Curriculum, and documents in soft copies are collected by using the google form link. These documents are stored in the personal storage of the Deputy Principal for Curriculum, so that teachers cannot re-manage their documents and cannot exchange information with each other. If the document is stored in personal storage, it is also prone to data loss and the search process will take time if a document will be needed. With these problems, a system is obtained that can create structured, effective and efficient storage in its use, where the data will be directly stored into the database. This filing system will be designed based on a website with the waterfall method. Aims to make it easier for teachers to exchange information and manage documents, which include being able to store documents, and search for the required documents quickly, also to make it easier Deputy Principal for Curriculum to make reports on collected documents, for evaluation materials in each new school year.